2014
DOI: 10.3109/08880018.2014.905666
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Families with a Child with Cancer

Abstract: The aim of this study was to identify and explore resilience factors associated with family adaption after a child had been diagnosed with cancer. Using a cross-sectional survey research design, parents (n = 26), and children (n = 25) from the same families independently completed six self-report questionnaires, as well as responded to an open-ended question about those qualities that helped their family through the period following the diagnosis. The most significant results came from the children's data. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(97 citation statements)
references
References 16 publications
7
61
0
18
Order By: Relevance
“…A secondary aim was to compare the identified resilience qualities in colored and black families. Previous research has emphasized the important role that routines and family time play in the process of adaptation by creating stability and continuity within the family system (Greeff & Van der Walt, 2010;. A strong positive correlation was also found in the present study between the routines and activities used by families and their level of adaptation.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…A secondary aim was to compare the identified resilience qualities in colored and black families. Previous research has emphasized the important role that routines and family time play in the process of adaptation by creating stability and continuity within the family system (Greeff & Van der Walt, 2010;. A strong positive correlation was also found in the present study between the routines and activities used by families and their level of adaptation.…”
Section: Discussionsupporting
confidence: 79%
“…Taanila et al (2002) found that family togetherness and cooperation, as well as time spent together, are especially important for families that have a child with a disability. These findings were also obtained in a study by Greeff and Van der Walt (2010) of families with an autistic child.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations